Introduction and spread of the cassava green mite, mononychellus tanajoa (Bondar) (Acari: Tetranychidae), an exotic pest in Africa and the search for appropriate control methods: a review - Yaninek , J.S.; Herren, H.R. (1988)
Mononychellus tanajoa (Bondar), a spider mite new to Africa, was discovered on cassava in Uganda in 1971. This exotic mite of Neotropical origin has since spread to 27 countries, causing an estimated 13–80% reduction in cassava yield. The history of its introduction and spread in Africa is reported, and present knowledge on the taxonomy, biology, ecology and pest status of the mite, and the evolution of strategies to control it are reviewed. While attempts have been made to control M. tanajoa, it remains a serious pest in most areas. The prospects for classical biological control as an appropriate control strategy are discussed.